2000
DOI: 10.5210/fm.v5i10.792
|View full text |Cite
|
Sign up to set email alerts
|

Free riding on Gnutella

Abstract: An extensive analysis of user traffic on Gnutella shows a significant amount of free riding in the system. By sampling messages on the Gnutella network over a 24-hour period, we established that almost 70% of Gnutella users share no files, and nearly 50% of all responses are returned by the top 1% of sharing hosts. Furthermore, we found out that free riding is distributed evenly between domains, so that no one group contributes significantly more than others, and that peers that volunteer to share files are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
783
0
13

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,153 publications
(813 citation statements)
references
References 7 publications
17
783
0
13
Order By: Relevance
“…c) Cooperation: All peers do not share the same number of files and do not exhibit the same "social behavior". As observed in [23], a large proportion of the user population is made of so-called free-riders, who do not make any file accessible to other users and essentially behave as clients. On the other hand, a small proportion of the users (less than 5%) contribute more than two thirds of the files shared in the system and essentially behave as servers.…”
Section: B) Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…c) Cooperation: All peers do not share the same number of files and do not exhibit the same "social behavior". As observed in [23], a large proportion of the user population is made of so-called free-riders, who do not make any file accessible to other users and essentially behave as clients. On the other hand, a small proportion of the users (less than 5%) contribute more than two thirds of the files shared in the system and essentially behave as servers.…”
Section: B) Contentmentioning
confidence: 99%
“…On the other hand, a small proportion of the users (less than 5%) contribute more than two thirds of the files shared in the system and essentially behave as servers. Based on the study in [23], we assign the following storage capacity to the peers in the network: 70% of the peers do not share any file (free-riders); 20% share 100 files or less; 7% share between 101 and 1, 000 files; finally, 3% of the peers share between 1, 001 and 2, 000 files (actual storage capacities are chosen uniformly at random). With this distribution, we have observed in our experiments a total storage capacity of more than 1, 600, 000 files, with more than 150, 000 distinct files being shared.…”
Section: B) Contentmentioning
confidence: 99%
“…Another type of locality characterizing peer-to-peer systems is the skewed level of service provided by different peers: a small number of peers respond to most queries, while a third to two thirds are "free riders" that do not contribute any service [14,311]. In particular, one study showed that the top responding peer could respond to nearly half of all queries.…”
Section: Peer-to-peer File Sharingmentioning
confidence: 99%
“…Examples include "weather" (14), "dictionary" (21), "lyrics" (64), and "horoscope" (86). Then there are quite a few nonsense queries, many of which are just parts of Internet addresses, such as "http" (13), ".com" (20), "www."…”
Section: Transactional Queriesmentioning
confidence: 99%
“…Incentives and micro-payments can be used to stimulate the users [1] and to avoid the free-riding phenomenon [2], and they are largely used in practice, e.g., BitTorrent [3], EMule [4] and Mojo-Nation 1 . In particular, a micro-payment scheme is an interesting alternative to a differential service incentives, especially when a market place is layered on top of a p2p system.…”
Section: Introductionmentioning
confidence: 99%